2021
DOI: 10.1101/2021.04.22.21255659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting a diagnosis of ankylosing spondylitis using primary care health records – a machine learning approach

Abstract: Ankylosing spondylitis is the second most common cause of inflammatory arthritis. However, a successful diagnosis can take a decade to confirm from symptom onset (via x-rays). The aim of this study was to use machine learning methods to develop a profile of the characteristics of people who are likely to be given a diagnosis of AS in future.The Secure Anonymised Information Linkage databank was used. Patients with ankylosing spondylitis were identified using their routine data and matched with controls who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Three health conditions affecting the nervous system were addressed [114][115][116], which were post stroke spasticity, epilepsy specifically mortality four years before and after its diagnosis (G40) [115], and a rare neurodegenerative disease progressive supra-nuclear palsy (G23) [116]. A few studies investigated musculoskeletal and The musculoskeletal and connective tissue condition were back pain (M54) prognosis within PHC settings [109], ankylosing spondylitis (M45) [110]. The gastrointestinal and kidney diseases were examined in four studies, namely inflammatory bowel diseases (K50-K52), including Crohn's disease and ulcerative colitis [26,71], peptic ulcers (K27)/gastroesophageal reflux (K21), and chronic kidney disease (N18) [90,133].…”
Section: Plos Onementioning
confidence: 99%
“…Three health conditions affecting the nervous system were addressed [114][115][116], which were post stroke spasticity, epilepsy specifically mortality four years before and after its diagnosis (G40) [115], and a rare neurodegenerative disease progressive supra-nuclear palsy (G23) [116]. A few studies investigated musculoskeletal and The musculoskeletal and connective tissue condition were back pain (M54) prognosis within PHC settings [109], ankylosing spondylitis (M45) [110]. The gastrointestinal and kidney diseases were examined in four studies, namely inflammatory bowel diseases (K50-K52), including Crohn's disease and ulcerative colitis [26,71], peptic ulcers (K27)/gastroesophageal reflux (K21), and chronic kidney disease (N18) [90,133].…”
Section: Plos Onementioning
confidence: 99%
“…Regarding musculoskeletal and connective tissue disorders [98][99][100][122][123][124], back pain (M54) prognosis within PHC settings could be predicted through focusing on patient function-related predictors more than on resolving pain [99]. A study revealed that models can be created using only data from medical records and had prediction values of 70-80% for identifying persons who are at risk of acquiring ankylosing spondylitis (M45) [100].…”
Section: Other Health Conditionsmentioning
confidence: 99%
“…Regarding musculoskeletal and connective tissue disorders [98][99][100][122][123][124], back pain (M54) prognosis within PHC settings could be predicted through focusing on patient function-related predictors more than on resolving pain [99]. A study revealed that models can be created using only data from medical records and had prediction values of 70-80% for identifying persons who are at risk of acquiring ankylosing spondylitis (M45) [100]. Two digestive health conditions were addressed in two studies [36,62], which were inflammatory bowel diseases (K50-K52), including Crohn's disease and ulcerative colitis, and peptic ulcers (K27)/gastroesophageal reflux (K21).…”
Section: Other Health Conditionsmentioning
confidence: 99%